Public finance : - Hyman, David N. (Thomson/South-Western, 2008)
Do not waste your time on this book! This book is poorly written. Mr. Hyman likes to hear himself talk and the presentation of material is redundant and poorly worded. Simple concepts are made more difficult than they need to be by long winded ramblings. Explanations are too wordy, contain too much unnecessary information, etc. The vast majority of the graphs have their descriptions on seperate pages that require the reader to flip between pages to compare the graphs to text. Many of the end of question practical problems are not even covered in the book. Some of the terms used in the problems are not even in the book. Economics can be a challenge at times anyway. This book just makes the journey more unpleasant than required.